Continuous-flow plasmapheresis in management of severe rhesus disease. Issue 6070 (7th May 1977) - Graham-Pole, J; Barr, W; Willoughby, M L
Abstract : Eight patients with severe rhesus disease and expected fetal loss were treated by intensive plasmapheresis using a continuous-flow cell separator. Plasmapheresis was started at 16-27 weeks' gestation, and continued until planned intrauterine transfusion or until the infant was delivered or the rhesus disease became uncontrolled again. Altogether 24 to 2371 of plasma was exchanged over periods ranging from seven to 16 weeks. In seven of the eight patients the anti-D concentration fell during the period of plasmapheresis. Amniotic fluid spectrophotometry values remained below those recorded in the preceding pregnancy in six out of seven women. In five patients an attempt was made to control the rhesus disease by plasmapheresis alone, and two of these women delivered infants who survived. In the other three cases the infants died, one from the idiopathic respiratory distress syndrome and the other two in utero. These preliminary findings suggest that intensive plasmapheresis with a cell separator may reduce fetal haemolysis is delivered. Nevertheless, plasmapheresis may best be used to reduce haemolysis until intrauterine transfusions may be given more safely after 30 weeks' gestation.